A study on Heavy Metal Contents in Cultivated Wild Ginseng from Korea and China - Jong-Yoon,Kim; Byung-Woo,Kim; Ki-Rok,Kwon (Korean Pharmacopuncture Institute, 2007)
Objectives : Heavy metal contents in cultivated wild ginseng from Korea and China were evaluated for the safety purpose. Methods : Arsenic(As), cadmium(Cd), lead(Pb), mercury(Hg), copper(Cu), chromium(Cr), and selenium(Se) from the root, stem, and leaves of the Korean cultivated wild ginseng and the root of the Chinese cultivated wild ginseng were analyzed for the existence of heavy metal contents. Results : Most of heavy metals weren't detected in all the samples. Copper and lead were found in very minute volume and didn't reach the toxic concentration level of 10mg/kg. Samples used in the test were grown in non-contaminated areas, free from heavy metal contamination. Conclusions : Based on above results, cultivated wild ginseng from Korea and China are relatively safe from the heavy metal exposure. But for more rigorous quality control, an epidemiological survey using the samples from more diverse areas should be conducted.